2017
DOI: 10.1016/j.pcl.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cholestasis

Abstract: Neonatal jaundice is common and usually not concerning when it is secondary to unconjugated hyperbilirubinemia, below the neurotoxic level, and resolves early. Primary care providers should be vigilant, however, about evaluating infants in whom jaundice presents early, is prolonged beyond 2 weeks of life, or presents at high levels. Even in well-appearing infants, fractionated (direct and indirect) bilirubin levels should be obtained in these clinical scenarios to evaluate for potential cholestasis. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 50 publications
0
33
0
7
Order By: Relevance
“…Genetic variants can explain normal or low serum γ‐glutamyltransferase (GGT) cholestasis in only 75% ~ 80% of paediatric patients 1 . Whole‐exome sequencing (WES) has identified several genes implicated in low‐GGT cholestasis, including USP53 , encoding a protein of uncertain function that associates with cell‐cell tight junctions, which was mutated in one family with cholestasis and hearing loss 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variants can explain normal or low serum γ‐glutamyltransferase (GGT) cholestasis in only 75% ~ 80% of paediatric patients 1 . Whole‐exome sequencing (WES) has identified several genes implicated in low‐GGT cholestasis, including USP53 , encoding a protein of uncertain function that associates with cell‐cell tight junctions, which was mutated in one family with cholestasis and hearing loss 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Infants with cholestasis should be evaluated promptly for potentially life-threatening and treatable causes whereby timing of intervention directly impacts clinical outcomes (7). Results of this study showed that most (60.8%) cholestatic infants had BA and INH.…”
Section: Discussionmentioning
confidence: 80%
“…O tempo menor de duração da colestase encontrado no estudo de Liu et al 16 pode ser decorrente do fato de ter sido considerado BD alterada > 2mg/dL. É importante ressaltar que o valor de BD como critério diagnóstico diverge na literatura, sendo considerado icterícia colestática BD > 1; 1,5 ou 2 mg/dl, como verificado nos estudos de Lane et al 10 , Albers et al 17 , Satrom et al 18 . O consenso mais recente de colestase elaborado pelas Sociedades Norte Americana e Europeia de Gastroenterologia, Hepatologia e Nutrição Pediátrica (NASPGHAN e ESPGHAN), conceitua colestase como valores de BD maior que 1mg/ dl independente do valor da bilirrubina total 5 .…”
Section: Resultsunclassified